2015
DOI: 10.1007/s11249-014-0458-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Subsurface Micro/Nano-Structural Evolution on Macroscopic Tribological Behavior of Ni3Al Matrix Composites

Abstract: The relationship between macroscopic tribological behavior and subsurface micro/nano-structural evolution needs to be studied in detail. We report here the results of dry sliding tribological tests of Ni 3 Al matrix composites with 1.5 wt% graphene nanoplatelets (GNPs) under different loads. We found that the friction coefficient decreased with increasing load, while the wear rate showed a downward trend after an initial increase. During the sliding wear process, severe plastic deformation and an accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…According to the research results of Zhai et al. 36 and Zhu et al., 37 the obtained approximate values of hardness and elastic modulus could be adopted to qualitatively characterize the material properties of wear scars. As shown in Tables 3 and 4, it can be found that the hardness and elastic modulus of NG have obvious improvement.…”
Section: Resultsmentioning
confidence: 99%
“…According to the research results of Zhai et al. 36 and Zhu et al., 37 the obtained approximate values of hardness and elastic modulus could be adopted to qualitatively characterize the material properties of wear scars. As shown in Tables 3 and 4, it can be found that the hardness and elastic modulus of NG have obvious improvement.…”
Section: Resultsmentioning
confidence: 99%
“…During the sliding process, the GNPs with a high hardness could be protected from the destruction of surface material. 35 Moreover, the high friction heat of the friction pair intensified the oxidation of the surface material. The increase in content of GNPs and oxides on the worn surface of GNMSCs was beneficial to the formation of the lubricating layer, which could reduce the friction coefficient and wear rate, leading to the excellent tribological performances.…”
Section: Effect Of Elastic Deformation On the Tribological Propertiesmentioning
confidence: 99%
“…It represents a significant advancement over traditional lubrication methods such as oil lubrication and grease lubrication, which are unable to solve the problems related to friction, wear and lubrication under extreme conditions such as high temperature and heavy load [1][2][3]. During dry sliding friction, the area formed on the worn surface and subsurface of the solid self-lubricating composites is called a friction interface layer in which the microstructure is different from the substrate [4][5][6][7]. The structural characteristics of the friction layer has an important influence on its tribological performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…The structural characteristics of the friction layer has an important influence on its tribological performance [6]. During sliding friction, the excellent antifriction and wear resistance of the friction interface layer are mainly because the subsurface friction action layer with excellent mechanical property supports the surface lubrication layer with good antifriction property [6][7][8][9][10]. In addition, the substrate layer acts as a support for the upper friction action layer, ensuring the overall strength of the material [6].…”
Section: Introductionmentioning
confidence: 99%